2012
DOI: 10.1177/1045389x12465134
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection of unidirectional carbon fiber–reinforced laminates with embedded magnetostrictive particulates: A preliminary study

Abstract: Defects in composite laminates are difficult to detect because of the conductive and paramagnetic properties of composite materials. Timely detection of defects in composite laminates can improve reliability. This research illustrates the preliminary analysis and detection of delaminations in carbon fiber laminate beams using a single layer of magnetostrictive particles and noncontacting concentric magnetic excitation and sensing coils. The baseline analytical models also begin to address the intrusive nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…In addition, the 300 mm particles size, which is larger than ply thickness (250 mm), may have exacerbated the loss in mechanical properties of the laminate. This observation is contrary to some studies (see Myers et al, 2012) that have shown that embedding TD particles increase the ultimate strength of CFRP systems without appreciable loss in stiffness. Table 1 shows the tensile test results obtained in this experiment.…”
Section: Static Testscontrasting
confidence: 85%
See 2 more Smart Citations
“…In addition, the 300 mm particles size, which is larger than ply thickness (250 mm), may have exacerbated the loss in mechanical properties of the laminate. This observation is contrary to some studies (see Myers et al, 2012) that have shown that embedding TD particles increase the ultimate strength of CFRP systems without appreciable loss in stiffness. Table 1 shows the tensile test results obtained in this experiment.…”
Section: Static Testscontrasting
confidence: 85%
“…Analytical and numerical models also exist to characterize the response of MS particles with respect to external magnetic field or load (Calkins et al, 2007;Carman and Mitrovic, 1995;Dapino et al, 2000Dapino et al, , 2002Datta et al, 2008;Myers et al, 2012;Zhou et al, 2013).…”
Section: Damage Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative relationship between the axial length of the excitation magnetic field and the excitation efficiency of the non-contact MsS used in GWT can only be obtained through experiments. A comprehensive finite element model or theoretical model [ 22 24 ], including all the parameters in the inspection progress, is needed for the quantitative analysis. This will be the topic in further research.…”
Section: Discussionmentioning
confidence: 99%
“…The test specimens were designed with dimensions that allowed nondestructive testing using the apparatus in Myers et al (2013), where the length and height dimensions were 9.75 in 3 1 in (247.65 mm 3 25.4 mm), respectively. The ply count is not constant as in Myers et al (2013) and ranges from 2 to 14 plies. The beams' dimensions were designed as in Myers (1996) to have a natural frequency of 10 Hz, but the ply counts vary along with the natural frequency for these specimens.…”
Section: Fabricationmentioning
confidence: 99%